2010
DOI: 10.3322/caac.20078
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Cancer: A Consensus Report

Abstract: Epidemiologic evidence suggests that cancer incidence is associated with diabetes as well as certain diabetes risk factors and treatments. This consensus statement of experts assembled jointly by the American Diabetes Association and the American Cancer Society reviews the state of science concerning 1) the association between diabetes and cancer incidence or prognosis; 2) risk factors common to both diabetes and cancer; 3) possible biologic links between diabetes and cancer risk; and 4) whether diabetes treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
1,078
7
20

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,100 publications
(1,126 citation statements)
references
References 117 publications
21
1,078
7
20
Order By: Relevance
“…A Danish study utilising a populationbased register (26) found that men and women with diabetes were at 10% increased risk but only hospitalised patients were included and diabetes status was ascertained using inpatient coding alone. Because of differences in apparent relationships between diabetes and the various types of malignancy, analyses of associations with all-cause cancers have been discouraged (8). However, the consistency of the results of this and other studies (22,23,24,26,27) suggests that there is a moderate diabetes-specific increase in overall cancer risk.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…A Danish study utilising a populationbased register (26) found that men and women with diabetes were at 10% increased risk but only hospitalised patients were included and diabetes status was ascertained using inpatient coding alone. Because of differences in apparent relationships between diabetes and the various types of malignancy, analyses of associations with all-cause cancers have been discouraged (8). However, the consistency of the results of this and other studies (22,23,24,26,27) suggests that there is a moderate diabetes-specific increase in overall cancer risk.…”
Section: Discussionmentioning
confidence: 81%
“…Associations between diabetes and cancer may, however, be confounded by co-incident risk factors including ageing, obesity and insulin resistance, an imprudent diet and lack of physical activity (8). In addition, some diabetes treatments may increase (9,10,11) or decrease (12) cancer risk.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes is an important risk factor for cardiovascular disease. Increasing evidence also relates diabetes to a higher risk of cancer, including cancers of the pancreas, endometrium, liver, colorectum, and breast, possibly by mechanisms related to hyperinsulinema, hyperglycemia, and chronic inflammation 46. Furthermore, some studies found that diabetes may increase mortality in patients with cancer 47.…”
Section: Discussionmentioning
confidence: 99%
“…Carstensen et al (2012) recently analyzed the effect of diabetes and diabetic therapy on cancer incidence in the Danish health system over a 27-year period and noted that the adverse effects of insulin treatment were quite modest. Therefore, caution has been advised in the acceptance of a cancer-promoting effect of insulin until further data are available (Gerstein 2010, Giovannucci et al 2010, Hernandez-Diaz & Adami 2010. Insulin therapy has also been associated with a greater than expected incidence of breast cancer and other malignancies (Home & Lagarenne 2009, Jonasson et al 2009), however, and insulin secretagogues have similarly been implicated in an increased incidence of PC.…”
Section: Proposed Mechanisms Of Diabetes-related Pancreatic Carcinogementioning
confidence: 99%